2014
DOI: 10.1186/preaccept-4938875171344463
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intra-operative blood loss and blood transfusion in orthognathic surgery: a retrospective cohort study in 92 patients

Abstract: Background: Patients undergoing orthognathic procedures can require blood transfusions. The objectives of this study were to evaluate the predictors of intra-operative blood loss in patients undergoing orthognathic procedures and the transfusion rates and practices of our institution. Materials and methods: This retrospective study included 92 patients who underwent the following four types of orthognathic procedures: Group 1, bimaxillary; Group 2, bimaxillary with bone grafts; Group 3, LeFort I osteotomies; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
2
2
0
Order By: Relevance
“…In this study, as the operation time increased, both the EIBL and RBL also increased. This is similar to the observations of several studies that reported that a longer operative time was associated with greater blood loss during orthognathic surgery 10–12,14–16 . As there was no interoperator variance in this study, the length of operative time is thought to be dependent on the complexity of the surgical plan.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, as the operation time increased, both the EIBL and RBL also increased. This is similar to the observations of several studies that reported that a longer operative time was associated with greater blood loss during orthognathic surgery 10–12,14–16 . As there was no interoperator variance in this study, the length of operative time is thought to be dependent on the complexity of the surgical plan.…”
Section: Discussionsupporting
confidence: 90%
“…Rummasak et al recommended that patients with lower body weight be prepared for transfusion due to the higher risk of blood loss 12,14 . However, other studies found no significant correlation between BMI and blood loss 11,17 . Considering that RBL reflects the patient's actual risk of blood loss, BMI is a significant predictor of bleeding risk during orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stehrer et al found that the amount of perioperative blood loss was 421.5 ml and bimaxillary group had more blood loss of 494.1 ml. 36 Similar to previous studies, 37,38 we found that intraoperative blood loss was an independent risk factor for autoblood reinfusion. However, the blood loss is difficult to predict before surgery.…”
Section: Discussionsupporting
confidence: 88%